Determinants of Indonesian Halal Food Exports: a Study on Crop Products in 1996-2021 - Lubis, Syauqi Ghufran; Riswanti Budi Sekarningsih (Sunan Kalijaga: Islamic Economics Journal, 2024)
This study examines Indonesia's halal food export value with a focus on crop products from 1990 to 2021. Indonesia, as a country with the largest Muslim population, has great potential in the global halal food market. However, challenges such as lack of halal product development and competition from other countries need to be overcome. This study uses time series data from the World Bank and applies the Autoregressive Distributed Lag (ARDL) model with Eviews 9 as an analysis tool to analyze the effect of capital, labor, economic openness, and inflation variables on export value. The results show that capital has a significant positive effect both in the short and long term, while labor shows a negative effect in the short term but positive in the long term. Economic openness has no significant effect on export value, while inflation shows a negative effect in the short run and positive in the long run on exports. This study provides insights into the factors affecting Indonesia's halal food exports and their implications in the context of international trade.